Teaching about the War: Primary school teachers and the 1879 War in the region of Tarapaca, Chile - Rivera Olguín, Patricio (2018)
The present article studies the perspectives of the education of the war of 1879 that develop the teachers of basic education of the region of Tarapacá in Chile. In this sense, teachers implement the school curriculum, textbooks and their contents so that basic education students acquire knowledge that will be internalized for the reproduction of Chilean citizenship in a space that was conquered in Peru during the war of the Peaceful. These contents constitute a way to socialize the Chilean national identity and the valuation of events and patriotic heroes of the conflict in order to generate identity and belonging links to the concept of homeland in the students through the war stories.